Integrated Total Quality Management Model from the Perspective of Islamic Education - Ulfah Hidayati (Global Education Journal, 2025)
This study aims to comprehensively examine the concept and implementation of the Total Quality Management (TQM) model from the perspective of Islamic education. TQM, as a managerial approach emphasizing the involvement of all organizational elements, process control, continuous improvement, and stakeholder satisfaction, is believed to offer effective solutions to the challenges of improving the quality of educational institutions. However, in the context of Islamic education, TQM cannot be applied mechanically as in industrial or business sectors; instead, it needs to be adapted to align with Islamic spiritual and moral values such as amanah (professional responsibility), ihsan (pursuit of excellence and perfection in work), and akhlaq (ethics and personal integrity). This research employs a qualitative-descriptive approach, utilizing an extensive literature review of studies and scientific publications from nationally accredited journals (Sinta 1-2) published between 2021 and 2025. The reviewed sources include empirical studies on the application of TQM in Islamic schools, madrasahs, pesantrens, and Islamic higher education institutions in Indonesia, as well as contemporary quality management theories relevant to Islamic values. The analysis maps the alignment between TQM principles, such as leadership, continuous improvement, customer focus, and teamwork, and Islamic management principles, including tauhid, syura, trust, and istikamah (steadfastness). The findings reveal that the implementation of TQM in Islamic educational institutions significantly contributes to academic quality enhancement, managerial efficiency, and the strengthening of value-based organizational culture. Institutions that integrate TQM principles with Islamic values show improvements in accreditation status, student satisfaction, teacher and lecturer productivity, and public trust. Moreover, the integration of spiritual values with modern management principles has proven to be a key factor in achieving competitive excellence and global relevance while maintaining Islamic identity. Therefore, this study emphasizes the importance of the Islamic Total Quality Management (TQM-I) model as a holistic quality management paradigm that not only focuses on achieving performance standards and efficiency but also on reinforcing the moral, spiritual, and social dimensions of education. This model serves as a strategic foundation for developing internal quality assurance systems across Islamic educational institutions, aiming to establish excellence, competitiveness, and a strong Islamic character.